Performance characteristics of TOP5 versus NOT-TOP5 races in female professional cycling - Lamberts, R. P.; van Erp, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Maximal mean power output (MMP) is commonly used to describe the demands and performances of races within professional male cycling. Within the female professional cyclist domain, however, there is limited knowledge regarding MMPs in races.1-4 Therefore, this study aims to describe MMPs within female professional cycling races whilst investigating differences between TOP5 and NOT-TOP5 races.